Archaeobotanical investigations at Danish urban sites: Planning and priorities - Earle Robinson, David (Hikuin, 1998)
The theme of this conference is topography and many papers deal with the location and structure of early urban sites in the landscape. In this contribution. I would like to address another important element in landscape archaeological studies - the vegetation. Specifically, I would like to examine the most effective ways in which we can investigate the special relationship between plant resources in the landscape in the past and the human populations which created, managed or exploited them. Plant resources, both in the form of cultivated plants and the natural vegetation, were a vital component in the development of early urban sites. If we can ascertain which of these resources were available, and the ways in which they were exploited, we can gain valuable insights into the internal workings of such settlements.